Job burnout and work values as antecedents of organizational citizenship behaviours / Shaiful Annuar Khalid et al. - Khalid, Shaiful Annuar; Abdul Rahman, Norshimah; Mat Noor, Ahmad Nizan; Sintha Madar, Abdul Rashid; Ibrahim, Nur Hazwani (Universiti Teknologi MARA, Perlis, 2016)
This study is conducted to examine the relationship between dimensions of job burnout, work values and organizational citizenship behaviour (OCB). Dimensions of burnout include cynicism, emotional exhaustion and reduced professional efficacy whereas work values consist of intrinsic work values and extrinsic work values. Two forms of OCBs tested are organizational citizenship behaviour directed at individual (OCBI) and organizational citizenship behaviour directed at organization (OCBO). The sample of this study includes 101 employees from several work divisions and levels of a Malaysian Multinational Corporation. It was found that dimensions of work values and burnout are significant factors to consider for enhancing OCBO. Specifically, the finding of this study demonstrates that intrinsic work values, extrinsic work values, emotional exhaustion and reduced professional efficacy are significant predictors of OCBO. However, only reduced professional efficacy significantly related with OCBI, whereas cynicism was not related with both types of OCB.